Diastolic Dysfunction, an Underestimated New Challenge in Dialysis. Issue 2 (25th September 2018) - Escoli, Rachele; Carvalho, Maria J; Cabrita, António; Rodrigues, Anabela
Abstract: Heart failure (HF) is very common in the general population and specifically in CKD patients due to higher prevalence of traditional and CKD‐related risk factors. In particular, HF with preserved ejection fraction (HFpEF) can affect over 50% of dialysis patients. However, little is known about this entity in CKD. It has been inadequately recognized over time and few data exist regarding clinical profiles and outcomes in dialysis patients. The aim of this paper is to do a critical appraisal of the diagnosis, clinical impact, and management of HFpEF with a focus on new diagnostic criteria and its impact on dialysis.